Functional Empowerment in People with Schizophrenia: A Case Study of Home-Based Family Supportive Therapy and Psychoeducation - Yudi Kurniawan; Indahria Sulistyarini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aims to evaluate the effectiveness of supportive therapy combined with family psychoeducation in treating a 32 years old male patient diagnosed with disorganized schizophrenia (F20.1). Disorganized schizophrenia is a subtype of schizophrenia characterized by behavioral disorganization, speech incoherence, and inappropriate affect, which often triggers stigma and a heavy burden of care for families. The participant exhibited clinical symptoms such as delusions of control (controlled by power of Ratu Kidul), auditory and tactile hallucinations, inappropriate affect (giggling), and sharp relational conflict with his stepfather. The intervention was carried out using a single case study design with Supportive Psychotherapy techniques that included emotional ventilation, reassurance, and persuasion, as well as environmental modification through family and community psychoeducation. The intervention results showed a significant decrease in positive and negative symptoms, increased insight, and improved social functioning. The client was able to control his emotions, establish more organized communication, and regain acceptance from his family and social environment. These findings confirm that a supportive therapy approach that integrates social and family support is highly effective in the functional recovery of psychotic patients with a dependent personality background and double-bind parenting style.